Human Trafficking Education for Emergency Department Providers - Shadowen, Caroline; Beaverson, Sarah; Rigby, Fidelma (Anti-Trafficking Review, 2021)
Many trafficked persons receive medical care in the Emergency Department (ED); however, ED staff have historically not been educated about human trafficking. In this article, we describe interventions aimed to train ED providers on the issue of trafficking. We performed a scoping review of the existing literature and found 17 studies that describe such interventions: 14 trainings implemented in the ED, two taught at conferences for ED providers, and one assessing a state-mandated training. These studies demonstrate that even brief education can improve provider confidence in screening and treating patients that experienced trafficking. We advocate for interventions to promote a team-based approach specific to the ED setting, acknowledge the importance of survivors’ input on curriculum development, and assess outcomes using pre- and post-surveys.